1990
DOI: 10.1111/myc.1990.33.7-8.411
|View full text |Cite
|
Sign up to set email alerts
|

Study of onychomycosis in India

Abstract: Fungal agents causing onychomycosis in an Indian population were studied in a hospital based study. It revealed that onychomycosis is more common in adult males, and that finger nails were more often affected compared with toe nails. Occupation did not seem to be related to infection. Trichophyton rubrum was the commonest fungus isolated (49.3%) followed by Candida species (23.2%). Four morphological varieties of Tr. rubrum colonies were observed but the role of a particular variety in causing chronic infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
34
3

Year Published

1994
1994
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 13 publications
(20 reference statements)
20
34
3
Order By: Relevance
“…This feature is consistent with some reports [9] but differs from others which show an increased prevalence of this disease in those aged > 50 years [13][14][15][16]. Children were the least affected group, which is in accordance with other studies [15].…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…This feature is consistent with some reports [9] but differs from others which show an increased prevalence of this disease in those aged > 50 years [13][14][15][16]. Children were the least affected group, which is in accordance with other studies [15].…”
Section: Discussionsupporting
confidence: 94%
“…Dermatophytes were isolated in 53 out of 202 cases, a gure comparable to those available in the existing data [9][10][11]. The clinical impression did not correspond to the laboratory ndings and the provisional diagnosis was con rmed in only 26% of cases.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In contrast Rigopoulos et al, (1998) and Madhuri et al, (2002) reported higher isolation rate of candida species in their study. Trichophyton rubrum (48.1%) remains the most common pathogenic fungus isolated in our study, in accordance with other studies (Vinod S at al, 2000;Banerjee et al, 1989). Puri D. K et al, (1998) reported Trichophyton mentagrophytes (50%) as the most common isolate followed by Trichophyton rubrum.…”
Section: Resultssupporting
confidence: 82%
“…Dermatophytes were the primary pathogens (79.6%) isolated in this study which is comparable with various studies (Pradnya Veer et al, 2007;Banerjee et al, 1989). In contrast Rigopoulos et al, (1998) and Madhuri et al, (2002) reported higher isolation rate of candida species in their study.…”
Section: Resultssupporting
confidence: 32%